The Colombian central board of hygiene, another victim of pandemic flu 1918-1919 - Martínez Martín, Abel Fernando; Meléndez Álvarez, Bernando Francisco; Manrique Corredor, Edwar Javier (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Objective: In this paper, through primary sources, we intend to clarify and specify the role and actions taken by the government against the flu pandemic of 1918 in Bogotá. Materials and methods: Primary Sources: Newspapers of the time in Bogota and Colombia, official reports of the Central Board of Hygiene, official reports of the Board of Relief and medical thesis, National University of Colombia. Also, secondary sources on the topic were reviewed. Conclusion: The Public Hygiene, headed by State, proved unable to deal with the pandemic. The Relief Board was the only institution that took effective action. This institution of private  character was created by the notables of the capital. The Board of Relief is remembered and praised by the print media, in contrast, the Central Board of Hygiene was represented as victim in the cartoons and was heavily criticized for their limited participation in the pandemic flu.